A Review of Substance Use Disorder Treatment in Developing World Communities - Jasleen Salwan; Craig L. Katz (Ubiquity Press, 2014)
Background: As global health endeavors increasingly encompass efforts to prevent and treat mental illness in the developing world, it is important to build a base of knowledge of existing treatment models and experimental outcomes. Objective: This article reviews the current literature on substance use disorder treatment in countries with a high, medium, or low Human Development Index according to the 2011 United Nations Development Programme Report. Methods: We searched the databases PubMed, PsycINFO, and Global Health using search terms such as 'substance abuse treatment developing countries', 'addiction developing nations', and 'alcohol abuse developing countries'. Opinion pieces and articles published before 1994 were excluded. Thirty relevant articles (excluding those reviewed for background information) were identified. Findings: Comprehensive overviews of treatment models were markedly absent from the current literature. However, existing research highlights specific areas of need, which may serve as a guide for future research and program development. Conclusions: In light of the evident need for treatment of substance use disorder in developing countries, future research would do well to blend inquiry with practice. Although further investigation is needed to fully understand the specific needs of developing world populations, assisting those populations should be a primary goal.